2014
DOI: 10.1038/ncomms6393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing AND gate genetic circuits based on CRISPR-Cas9 for identification of bladder cancer cells

Abstract: The conventional strategy for cancer gene therapy offers limited control of specificity and efficacy. A possible way to overcome these limitations is to construct logic circuits. Here we present modular AND gate circuits based on CRISPR-Cas9 system. The circuits integrate cellular information from two promoters as inputs and activate the output gene only when both inputs are active in the tested cell lines. Using the luciferase reporter as the output gene, we show that the circuit specifically detects bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 29 publications
1
153
0
1
Order By: Relevance
“…The dCas9 has been used for transcriptional activation and repression [134][135][136][137], for localizing fluorescent protein labels [138], and for recruiting histone modifying enzymes [139,140]. Other applications of Cas9 include building gene circuits [141][142][143], creating new anti-microbials [144], antivirals [145][146][147], and large-scale gain-and loss-of-function screening [148][149][150][151] (Table 1).…”
Section: Genome Editing Applicationsmentioning
confidence: 99%
“…The dCas9 has been used for transcriptional activation and repression [134][135][136][137], for localizing fluorescent protein labels [138], and for recruiting histone modifying enzymes [139,140]. Other applications of Cas9 include building gene circuits [141][142][143], creating new anti-microbials [144], antivirals [145][146][147], and large-scale gain-and loss-of-function screening [148][149][150][151] (Table 1).…”
Section: Genome Editing Applicationsmentioning
confidence: 99%
“…Zalatan et al reprogrammed a branched metabolic pathway in yeast to control the production of various product metabolites (30). Liu et al used a nuclease Cas9 to create a promoter-based "AND" logic gate to identify and control a specific type of cancer cell (34). Promoter-based logic gates (e.g., AND, OR, and NOT) could also be combined with the scRNA components to create complex regulatory patterns that are induced only under certain conditions.…”
Section: Engineering Complex Regulatory Patterns Using Crispra/imentioning
confidence: 99%
“…[7][8][9][10][11][12] However, mutation of lncRNAs will cause cancer initiation and promote the metastasis of malignancy. [13][14][15] For instance, lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was first found in lung cancer metastasis. Many studies had demonstrated that lncRNA MALAT1 was overexpressed in various cancer, and it might act as a potential biomarker and therapeutic target in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%